SYNTHESIS AND BIOLOGICAL ACTIVITIES OF COBALT COMPLEX WITH SCHIFF’SBASE LIGAND DERIVED FROM 4-CHLORO-N-[(E)-PYRIDIN-2-YLMETHYLIDENE] ANILINE - D. DHAGE, SURESH (Innovare Journal of Sciences, 2020)
4-chloro-N-(E)-pyridin-2-ylmethylidene aniline isprepared by condensing 2-pyridine carboxaldehyde and 4-chloroanilinein ethanol. The Schiff base was reacted with cobalt chloride in acetonitrile and solution of two equivalent of triphenylphospine to obtain the corresponding Cobalt4-chloro-N- [(E)-pyridin-2-ylmethylidene]aniline complex. The synthesised Schiff base and complex were characterized on the basis of their chemical properties and spectroscopic data. These compounds were tested for anticancer,anti-inflammatory activity and antimicrobial activity against a variety of test organisms: Escherichia coli, Staphylococcus aureus, and Candida albicans. The compounds containing chlorogroup as substituents on the phenyl ring have been found to be very effective antimicrobial agents.